Family of Distributions Derived from Whittaker Function - Maha A. Omair; Yusra A. Tashkandy; Sameh Askar; Abdulhamid A. Alzaid (Mathematics, 2022)
In this paper, we introduce a general family of distributions based on Whittaker function. The properties of obtained distributions, moments, ordering, percentiles, and unimodality are studied. The distributions’ parameters are estimated using methods of moments and maximum likelihood. Furthermore, a generalization of Whittaker distribution that contains a wider class of distributions is developed. Validation of the obtained results is applied to real life data containing four data sets.